2016
DOI: 10.1016/j.jpsychires.2015.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Sedation mediates part of Citalopram's effect on agitation in Alzheimer's disease

Abstract: Background We found a benefit of citalopram for agitation in the Citalopram for Agitation in Alzheimer’s Disease study (CitAD), and wondered if this was mediated by a sedative effect. CitAD was a randomized, placebo-controlled, double-blind, parallel group trial conducted at 8 academic centers in the United States and Canada from August 2009 to January 2013. One hundred sixty-two participants with probable Alzheimer’s disease (AD) and clinically significant agitation were analyzed in this study. Participants r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Treatment options for behavioral and psychological symptoms of dementia (BPSD; eg antipsychotics) have modest evidence for efficacy and have significant limitations, including the propensity to increase metabolic disorders, falls, drug interactions, and mortality 25-28. Citalopram has been studied in several capacities29-35 regarding its potential to manage multiple manifestations of BPSD (Table 2). The exact mechanism of how citalopram is efficacious for BPSD is largely unknown; however, it is likely not owed completely to sedation 29…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment options for behavioral and psychological symptoms of dementia (BPSD; eg antipsychotics) have modest evidence for efficacy and have significant limitations, including the propensity to increase metabolic disorders, falls, drug interactions, and mortality 25-28. Citalopram has been studied in several capacities29-35 regarding its potential to manage multiple manifestations of BPSD (Table 2). The exact mechanism of how citalopram is efficacious for BPSD is largely unknown; however, it is likely not owed completely to sedation 29…”
Section: Resultsmentioning
confidence: 99%
“…Citalopram has been studied in several capacities29-35 regarding its potential to manage multiple manifestations of BPSD (Table 2). The exact mechanism of how citalopram is efficacious for BPSD is largely unknown; however, it is likely not owed completely to sedation 29…”
Section: Resultsmentioning
confidence: 99%
“…The authors further suggested that those with moderate agitation but less cognitive impairment were more likely to obtain benefits from citalopram, whereas more severe cases, especially dementia patients, could be at higher risk of sleep disturbances [ 103 ]. In a secondary analysis, the benefits of citalopram were only partially (11%) due to sedation, and largely due to unknown mechanisms [ 104 ].…”
Section: Symptomatic Treatmentsmentioning
confidence: 99%
“…3,4 Citalopram was shown to be beneficial for agitation, aggression, irritability and other neuropsychiatric symptoms in Alzheimer's disease. 5 Siddique et al evaluated the effectiveness of citalopram in Alzheimer's disease by using a neuropsychiatric inventory in their study named Clinical Antipsychotic Trials of Intervention Effectiveness in Alzheimer's Disease. Their retrospective analyses showed that it is beneficial for the treatment of those with agitation, delusion, hallucination, depression, aggression, euphoria, disinhibition, irritability, apathy, abnormal motor behavior, sleep and appetite.…”
Section: Remission In Visual Hallucinatory Experiences After Citaloprmentioning
confidence: 99%